Comprehensive sustainability reporting: A long road to go for German TecDax 30 companies - Avo Schönbohm; Ulrike Hofmann (Hochschule für Wirtschaft und Recht Berlin, IMB Institute of Management Berlin, 2012)
This study analyses the current practice in sustainability reporting among the German TecDAX companies for 2009 and 2010. A scoring system has been developed with 23 indicators based on the guidelines of the Global Reporting Initiative to evaluate scope and quality of the sustainability reports. This study reveals that most of the companies do not publish meaningful, comparable and transparent reports. Almost half of the TecDAX companies do not publish any information about their impact on society, environment and economy. The majority of the published reports does not enable the recipients of the report to develop a comprehensive picture of the socio-ecological impact and hence are not adequate. Some reports even raise the suspicion of green washing. In this case, sustainability reporting fails to have the desired positive effect for the company and can lead to a negative image. – – Diese Studie analysiert die aktuelle Praxis des nachhaltigen Reportings unter den deutschen TecDAXUnternehmen in den Jahren 2009 und 2010. Ein Auswertungssystem mit 23 Indikatoren, die auf den Richtlinien der Global Reporting Initiative basieren, wurde entwickelt um die Bandbreite und Qualität der Nachhaltigkeitsberichte zu evaluieren. Diese Studie macht deutlich, dass die meisten Unternehmen keine aussagekräftigen, vergleichbaren und transparenten Geschäftsberichte publizieren. Fast die Hälfte der TecDAX-Unternehmen veröffentlichen überhaupt keine Information über die Auswirkungen ihres Geschäftshandelns auf Gesellschaft, Umwelt und Wirtschaft. Die Mehrheit der Geschäftsberichte erlaubt es den Lesern nicht, ein umfassendes Bild des sozio-ökologischen Einflusses zu bekommen, diese sind daher nicht adequat. Ein Teil der Geschäftsberichte legt sogar den Verdacht des Greenwashings nahe. In diesem Falle gelingt es dem Nachhaltigkeits-Berichtwesen nicht, die erwünschten positiven Auswirkungen auf das Unternehmen zu bewirken, was eventuell sogar zu einem negativen Image führen kann.
Keywords: 330